Favorite stories from Cowgirl Kate and Cocoa : spring babies - Silverman, Erica (Green Light reader., 2016)
"Cowgirl Kate is excited about the arrival of all the baby animals. Her best friend, Cocoa the horse, is not so excited. Babies are a lot of work! But maybe with Cowgirl Kate's help, Cocoa will discover that it can be a lot of fun to welcome new friends to the ranch."--Page 4 of cover.